1989
DOI: 10.2307/3430541
|View full text |Cite
|
Sign up to set email alerts
|

Furnace-Generated Acid Aerosols: Speciation and Pulmonary Effects

Abstract: Guinea pigs were exposed to ultrafine aerosols (< 0.1 ,Im) of zinc oxide with a surface layer of sulfuric acid. These acid-coated aerosols are typical of primary emissions from smelters and coal combustors. Repeated daily 3-hr exposures for 5 days produce decrements in lung volumes and pulmonary diffusing capacity and elevations of lung weight/body weight ratio, protein, and number of neutrophils in pulmonary lavage fluid at concentrations of 20 ,ug/m3. A single 1-hr exposure to 20 ,ug/m3 causes increased bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
0
20
0
1
Order By: Relevance
“…Acidity (24,25), transition metals (26)(27)(28), endotoxin (29), and particle size (30,31) have been associated with the inflammatory responses of airways. However, it is not clear if components and size of particles affect heart rate and blood pressure through similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Acidity (24,25), transition metals (26)(27)(28), endotoxin (29), and particle size (30,31) have been associated with the inflammatory responses of airways. However, it is not clear if components and size of particles affect heart rate and blood pressure through similar mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this type of study involved supplying fresh laboratory-generated coal fly ash particles to animal inhalation chambers as part of a study of the combined effects of H 2 SO 4 and coal fly ash. 25,376 Inhalation studies involving ultrafine and nanoparticle PM also require having a laboratory particle generator connected to the inhalation chamber due to the rapid transformation of the particles by coagulation. 377 Surrogate particle inhalation studies require close cooperation between the life sciences and aerosol team members as well as physical proximity of the animal care and combustion facilities.…”
Section: Controlled Exposure To Concentrated Ambient Particlesmentioning
confidence: 99%
“…Short-term sulfuric acid exposures between 0.1 and 1.0 mg/m3 have produced lung clearance function and pulmonary mechanical effects in normal and asthmatic human subjects (10,11). Animal studies have also shown adverse effects from exposure to acid aerosols such as clearance abnormalities (12), airway hyperresponsiveness and secretory cell hyperplasia (13), and changes in pulmonary function (14). However, the potential for neutralization of acidic aerosols by endogenous respiratory tract ammonia plays a complex and uncertain role in the toxicity of acidic aerosols (15,16).…”
mentioning
confidence: 99%
“…Clearance abnormalities may result from changes in viscosity in acidic mucous versus alkaline mucous (43). Changes in lung function and airway hyperresponsivity observed in guinea pigs (44,45) …”
mentioning
confidence: 99%